Valid and reliable instrument for measuring Indonesian students’ reading literacy - Kharismawati, Limala Ratni Sri; Widodo, Pratomo; Retnawati, Heri (Intelektual Pustaka Media Utama, 2024)
The study aims to verify the validity and reliability of a set of tests for measuring Indonesian students’ reading literacy achievement that has been developed by the Center for Language Strategy and Diplomacy Development as well as the Educational Assessment Center, two institutions under the auspices of the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia. The construct validity of the test was verified using confirmatory factor analysis (CFA) and the reliability was estimated using the composite reliability (CR) formula. The data used were responses from a sample of 6,539 students from 294 high schools in 34 provinces in Indonesia. The sample was established using a multistage sampling technique from the study population of 15-year-old students in Indonesia. The results indicated that the construct validity of the test was verified and the reliability coefficient was 0.805, which was defined good. Based on the results, it can be concluded that the set of tests is appropriate to be used to measure Indonesian students’ reading literacy achievement. In other words, using the set of tests will establish measurement that can reflect the reading literacy achievement of Indonesian students.